PENGARUH KINERJA CORPORATE SOCIAL RESPONSIBILITY TERHADAP PERSISTENSI LABA PADA PERUSAHAAN YANG BERGERAK DI SEKTOR BARANG KONSUMSI DENGAN SUBSEKTOR FARMASI, KOSMETIK DAN KEPERLUAN RUMAH TANGGA DAN PERALATAN RUMAH TANGGA YANG TERDAFTAR DI BURSA EFEK INDONE - Shenjaya, Silviana (Business Accounting Review, 2016)
Researches on the affect of CSR on financial performance (that is periodic) such as ROA, ROE, ROI, ROS and EBIT have been done before. However, researches on the affect of CSR on the persistence of earnings were still very little : Riahi and Belkaoui (2004), Lakshman and Yang (2009), and Lassad and Khamoussi (2012) and had never been done in Indonesianâs companies especially in consumer goods sector, especially in pharmaceuticals, cosmetics and household and household appliances. The research objective was to know whether CSR affected the persistence of earnings in companies engaged in the consumer goods sector in the fields of pharmaceuticals, cosmetics and household and household appliances.This research was conducted on Indonesianâs companies, especially in consumer goods sector in pharmaceuticals, cosmetics and household and household appliances that had already been doing CSR from 2010 to 2014. CSR was measured based on the GRI reporting criteria version 3.1. Meanwhile, earnings persistence was measured by using the slope of the earnings per share. This study used several control variables such as operating cycle, sales volatility, cash flow volatility, proportion of negative income, firm size and competition intensity.This research used a sample of 60 companies year by using multiple linear regression with SPSS. The results of the study had not (managed to) shown a significant affect between CSR and persistence of earnings. The research also had not found yet a significant relationship between sales volatility, cash flow volatility, proportion of negative income, firm size, and competition intensity with earnings persistence. However, the operating cycle was found to have significantly affecting to persistence of earnings.